Generalized expectancies for negative mood regulation and major depressive disorder: the role of previous depressive episodes and comorbid mental disorders - Pfeiffer, Nils; Kämmerer, Annette; Mearns, Jack; Catanzaro, Salvatore J.; Backenstraß, Matthias (Psychopathology, 2011)
BACKGROUND: Generalized expectancies for negative mood regulation (NMR) have important consequences for the ability to regulate negative mood. This study tests two resulting hypotheses. NMR expectancies should correlate with the number of previous depressive episodes. Furthermore, there should be a correlation between NMR expectancies and the number of DSM-IV axis I disorders comorbid to depression. In order to test these hypotheses with an efficient instrument, this article presents the NMR-SF as a short form of the NMR Scale. - METHODS: During inpatient treatment, a sample of 40 depressed patients was interviewed by a clinical psychologist with the Structural Clinical Interview for DSM-IV to assess the number of previous depressive episodes as well as the number of axis I comorbidities. Patients completed the NMR-SF to measure NMR expectancies. Additionally, a nonclinical sample of 560 participants completed the NMR-SF to test its reliability and validity. - RESULTS: The findings indicate that the NMR-SF is reliable and valid. In the clinical sample, NMR expectancies did not correlate significantly with the number of previous depressive episodes. There was a significant correlation between NMR expectancies and the number of comorbid mental disorders. - CONCLUSION: Previous depressive episodes do not seem to result in lower NMR expectancies. The findings are in line with the hypothesis that NMR expectancies are involved in the etiology of mental disorders comorbid to depression.